Catholic almanac. - Foy, Felician A.; Our Sunday Visitor, Inc.; St. Anthony's Guild (Huntington, Ind. Our Sunday Visitor)
Annual.
Editor: 1969- F. A. Foy.
The most complete one-volume source of facts and information on the Catholic Church.
Vols. for 1969-71 published by the St. Anthony's Guild, Paterson, N.J., and distributed by Doubleday & Co., Garden City, N.Y.
Keywords: Catholic almanacs -- United States